2020
DOI: 10.1093/brain/awaa227
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in neuromyelitis optica: a link between astrocytopathy and demyelination

Abstract: Neuromyelitis optica, a rare neuroinflammatory demyelinating disease of the CNS, is characterized by the presence of specific pathogenic autoantibodies directed against the astrocytic water channel aquaporin 4 (AQP4) and is now considered as an astrocytopathy associated either with complement-dependent astrocyte death or with astrocyte dysfunction. However, the link between astrocyte dysfunction and demyelination remains unclear. We propose glial intercellular communication, supported by connexin hemichannels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Another possibility that may be directly related to the expression of AQP4–IgG is the involvement of connexins, closely related to cell adhesion molecules, in the possible origin of the irregular shape of the neurospheres. The alterations observed in their shape, as well as the presence of anti-vascular endothelial IgG, or alterations in glutamate cytotoxicity, may influence the loss of oligodendrocytes and their myelinic potential [ 7 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility that may be directly related to the expression of AQP4–IgG is the involvement of connexins, closely related to cell adhesion molecules, in the possible origin of the irregular shape of the neurospheres. The alterations observed in their shape, as well as the presence of anti-vascular endothelial IgG, or alterations in glutamate cytotoxicity, may influence the loss of oligodendrocytes and their myelinic potential [ 7 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is that remyelination is thought to be limited in NMOSD, and no treatments are able to restore myelin; however, the use of drugs that may favor remyelination is being considered for the treatment of multiple sclerosis [ 13 ], and it has also been suggested that they may promote remyelination in NMOSD, as early loss of oligodendrocytes (OLG) has been reported [ 14 , 15 , 16 , 17 ]. Other authors have reported that NMO–IgG may decrease the expression of connexins and cause oligodendrocyte damage and demyelination in NMOSD [ 18 ]. For instance, clobetasol, which promotes OLG differentiation [ 19 ], has been analyzed in an in vivo NMOSD model, with promising results.…”
Section: Introductionmentioning
confidence: 99%
“… 70 AQP4-null mice appear normal neurologically but, unlike wild-type mice, their motor performance does not improve with Rotarod training. 11 Richard et al 71 reported altered expression and function of astrocytic connexins after application of NMO-IgG. As components of tripartite CNS synapses, and the anatomical basis of the connexin-sustained astroglial syncytium that regulates the flow of water and small molecules throughout the CNS, astrocytes are crucial for synaptic plasticity and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system that is associated with serum aquaporin-4 antibodies (AQP4-IgG) directly against the AQP4 channels on the foot processes of astrocytes ( 1 ), clinically with serious optic neuritis (ON), longitudinally extensive transverse myelitis (LETM), and intractable nausea, vomiting, and hiccups induced by area postrema syndrome (APS) as the main manifestations ( 2 ). AQP4-IgG is the amplification of inflammation that mediates the damage of the blood–brain barrier (BBB), astrocyte injury, subsequent demyelination, and finally the occurrence and development of NMOSD ( 3 ). Therefore, AQP4-IgG is considered a pathogenic marker of NMOSD, and the presence of AQP4-IgG unequivocally distinguishes NMOSD from multiple sclerosis (MS) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%